2020
DOI: 10.20944/preprints202005.0479.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Open Source High-Temperature RepRap for 3-D Printing Heat-Sterilizable PPE and Other Applications

Abstract: Thermal sterilization is generally avoided for 3-D printed components because of the relatively low deformation temperatures for common thermoplastics used for material extrusion-based additive manufacturing. 3-D printing materials required for high-temperature heat sterilizable components for COVID-19 and other applications demands 3-D printers with heated beds, hot ends that can reach higher temperatures than polytetrafluoroethylene (PTFE) hot ends and heated chambers to avoid part warping and delamination. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…A limiting factor in the production of alternative biomaterials for alternative to single-use PPE relates to thermal stability of materials for fabrication and potential for deformation due to thermal processes. Skrzypczak et al (2020) recently reported on a new 3D printing approach for meeting such a need where they described an affordable, self-replicating, rapid prototyper that would also make this approach more accessible to home-based 3D printing activities. Chen et al (2019) also demonstrated potential for exploiting different forms of polymer processing (such as 3D printing and injection moulding) after novel vapour hydrogen peroxide and electron beam treatments that could be advance next-generation PPE and medical device technologies.…”
Section: Waste Management Resource Utilization and Environmental Impmentioning
confidence: 99%
“…A limiting factor in the production of alternative biomaterials for alternative to single-use PPE relates to thermal stability of materials for fabrication and potential for deformation due to thermal processes. Skrzypczak et al (2020) recently reported on a new 3D printing approach for meeting such a need where they described an affordable, self-replicating, rapid prototyper that would also make this approach more accessible to home-based 3D printing activities. Chen et al (2019) also demonstrated potential for exploiting different forms of polymer processing (such as 3D printing and injection moulding) after novel vapour hydrogen peroxide and electron beam treatments that could be advance next-generation PPE and medical device technologies.…”
Section: Waste Management Resource Utilization and Environmental Impmentioning
confidence: 99%
“…If the device is used on multiple patients, the pump and hose should be sanitized with ethylene oxide if made of silicone materials [52] or steam for fluoroplastics [53]. As 3-D printed components are very porous [54], they can be hard to sanitize fully, and therefore a new mouthpiece should be used for each patient unless printed in hightemperature plastics that can be sterilized with heat [55].…”
Section: Reuse Potential and Adaptabilitymentioning
confidence: 99%
“…Distributed manufacturing of open hardware has been shown to be an effective means to meet demand for a wide array of medical supplies during this immense supply shortages observed in the current pandemic [104][105][106][107][108][109][110][111][112][113][114].…”
Section: Safetymentioning
confidence: 99%